Enhancing Dealer Satisfaction: Assessing Durability and Business Support of LG Products in Ahmedabad - Gohel, Bhoomika; Yadav, Vyom; Vidani, Jignesh (Journal of Advanced Research in Service Management, 2023)
Marketing is a communication process with the goal of allowing individuals or groups to purchase products and services that may satisfy their current or newly determined needs or desires. The purpose of this report was to determine the level of dealer satisfaction with LG electronics. To investigate the factors influencing LG electronics retailers .The study focused on numerous areas where LG electronics could be improved from the perspective of dealers. The study also investigated the close impact of sales promotion on sales. The study was carried out through data analysis and interpretation, which revealed that the majority of the dealers have 10-15 years of expertise in cement dealership, with some dealers dealing with LG electronics for more than ten years. Most merchants are pleased with the quality of the cement and rank the brand highly. Discounts were the most important promotional aspect that drove retailers to adopt LG electronics. According to dealers, outdoor advertising and electronic media are more efficient ways to promote LG products Promotional plans and company service are the most important supports that dealers require. According to the survey, dealers should be encouraged by organizing special meetings and engagements. The majority of the merchants recommended nice and modern products. Promotional activities such as discounts, gifts, and prizes might be improved. This study also stated that because media has a greater impact, companies should invest in more mass media and outdoor commercials to promote their brand. Service delivery time should be improved. Improvements in recognizing the merchants with the largest annual sales turnover. Regular feedback could be enhanced as well. The majority of dealers indicate that the product’s price is below the acceptable threshold. The corporation should provide a reasonable credit period to its dealers so that both the company and the dealers’ profit.